Cellular Base of Mint Allelopathy: Menthone Affects Plant Microtubules - Sarheed, Mohammed Mahmood; Rajabi, Fatemeh; Kunert, Maritta; Boland, Wilhelm; Wetters, Sascha; Miadowitz, Kai; Kaźmierczak, Andrzej; Sahi, Vaidurya Pratap; Nick, Peter (Frontiers in Plant Science, 2020)
Plants can use volatiles for remote suppression of competitors. Mints produce essential oils, which are known to affect the growth of other plants. We used a comparative approach to iden-tify allelopathic compounds from different Mints (genus Mentha, but also including Cat Mint, Nepeta cataria, and Corean Mint, Agastache rugosa, belonging to sisters clades within the Mentheae) using the standard cress germination assay as readout. To understand the mechanism behind this allelopathic effect, we investigated the response of tobacco BY-2 cell lines, expres-sing GFP-tagged markers for microtubules and actin filaments to these essential oils. Based on the comparison between bioactivity and chemical components, we identified menthone as prime candidate for the allelopathic effect, and confirmed this bioactivity targeted to microtubules experimentally in both, plant cells (tobaccoBY-2), and seedlings (Arabidopsis thaliana). We could show that menthone disrupted microtubules and induced mortality linked with a rapid permeabilisation (less than 15 min) of the plasma membrane. This mortality was elevated in a tu-bulin marker line, where microtubules are mildly stabilised. Our study paves the way for the development of novel bioherbicides that would be environmentally friendly.